RELIABILITY OF THE INSTRUMENT WITH CRONBACH'S ALPHA AND VALIDATION OF THE HYPOTHESIS BY ANOVA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this research is to verify the reliability of the instrument used to collectthe information, applying Cronbach's Alpha, and the validation of the hypothesisthrough an Analysis of Variance (ANOVA). Cronbach's Alpha is obtained in Excel. Thesurvey is used with the questions shown in the Check List, applied in a vehicleassembly plant. The instrument used and the validation of the hypothesis are subjects ofa research work, referring to the production planning in the vehicle assembler CiautoCia. Ltda. specifically for the HAVAL M4 AC 1.5 TM 5P 4X2 Model, where for theverification of the reliability of the instrument used a Cronbach's Alpha of 0.57 wasobtained, which indicates that the instrument used has a poor reliability according to thescale in the Cronbach's Reliability table. As for the validation of the hypothesis byapplying an ANOVA, a calculated F - Fisher of 28.25 was obtained, compared to atabulated F - Fisher of 2.996, so the null hypothesis (H0) should be rejected in favor ofthe alternative hypothesis (Ha).